2013
DOI: 10.1177/0957650912470913
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between modeling and experiments on a two-stage rotary vane expander for an HFC-410A air conditioning system

Abstract: Substituting throttle valve with expander can effectively enhance the performance of a refrigeration system. A novel rotary vane expander with two-stage internal expansion was developed for HFC-410A air conditioning system. The structural characteristics and operating principle of the expander are presented. A simulation model including thermodynamic and dynamic calculations is established. An HFC-410A air conditioning system was built for the purposes of testing the prototype and verifying the model. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…With a conventional refrigerant (R-410A), the maximum reported expander efficiency is 61% with a rotary vane expander (Xia et al, 2013). The highest COP improvement measurement reported for a CO 2 system was approximately 30% (Kohsokabe et al, 2006;Kakuda et al, 2009) and for a non-CO 2 system (R-410A) was 10.3% (Wang et al, 2013). A summary of various expander experimental data available in the literature is tabulated in Tables 1-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a conventional refrigerant (R-410A), the maximum reported expander efficiency is 61% with a rotary vane expander (Xia et al, 2013). The highest COP improvement measurement reported for a CO 2 system was approximately 30% (Kohsokabe et al, 2006;Kakuda et al, 2009) and for a non-CO 2 system (R-410A) was 10.3% (Wang et al, 2013). A summary of various expander experimental data available in the literature is tabulated in Tables 1-3.…”
Section: Discussionmentioning
confidence: 99%
“…From their simulation, it was found that the expander could improve the system's COP improvement by 6-22%, depending on the condensation temperature and the expander's inlet degree of subcooling. A year later, Wang et al (2013) reported further a further study, comparing modeling data with and experimental. This study found that even with R-410A as the refrigerant, the expander could improve the COP by 10.3% as compared to a…”
Section: Vane Expander 331 Rotary Vane Expandermentioning
confidence: 97%
“…The inlet is considered to be a Borda-Carnot-type restriction with constant c q discharge or loss coefficient which is a predefined parameter. The mass-flow rate can be estimated by the following equation (4).…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…When the position of the valve is given, the mass flow across the valve can be calculated using also equation (4). Valve mass (m v ), the viscous coefficient (k v ), and valve spring stiffness (C) are predefined for the system.…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation